Promotion of mental health in young adults via mobile phone app: Study protocol of the ECoWeB (emotional competence for well-being in Young adults) cohort multiple randomised trials - Newbold, A.; Warren, F. C.; Taylor, R. S.; Hulme, C.; Burnett, S.; Aas, B.; Botella, C.; Burkhardt, F.; Ehring, T.; Fontaine, J. R.J.; Frost, M.; Garcia-Palacios, A.; et al. (BMC Psychiatry, 2020)
Background: Promoting well-being and preventing poor mental health in young people is a major global priority. Building emotional competence (EC) skills via a mobile app may be an effective, scalable and acceptable way to do this. However, few large-scale controlled trials have examined the efficacy of mobile apps in promoting mental health in young people; none have tailored the app to individual profiles. Method/design: The Emotional Competence for Well-Being in Young Adults cohort multiple randomised controlled trial (cmRCT) involves a longitudinal prospective cohort to examine well-being, mental health and EC in 16-22 year olds across 12 months. Within the cohort, eligible participants are entered to either the PREVENT trial (if selected EC scores at baseline within worst-performing quartile) or to the PROMOTE trial (if selected EC scores not within worst-performing quartile). In both trials, participants are randomised (i) to continue with usual practice, repeated assessments and a self-monitoring app; (ii) to additionally receive generic cognitive-behavioural therapy self-help in app; (iii) to additionally receive personalised EC self-help in app. In total, 2142 participants aged 16 to 22 years, with no current or past history of major depression, bipolar disorder or psychosis will be recruited across UK, Germany, Spain, and Belgium. Assessments take place at baseline (pre-randomisation), 1, 3 and 12 months post-randomisation. Primary endpoint and outcome for PREVENT is level of depression symptoms on the Patient Health Questionnaire-9 at 3 months; primary endpoint and outcome for PROMOTE is emotional well-being assessed on the Warwick-Edinburgh Mental Wellbeing Scale at 3 months. Depressive symptoms, anxiety, well-being, health-related quality of life, functioning and cost-effectiveness are secondary outcomes. Compliance, adverse events and potentially mediating variables will be carefully monitored. Conclusions: The trial aims to provide a better understanding of the causal role of learning EC skills using interventions delivered via mobile phone apps with respect to promoting well-being and preventing poor mental health in young people. This knowledge will be used to develop and disseminate innovative evidence-based, feasible, and effective Mobile-health public health strategies for preventing poor mental health and promoting well-being. Trial registration: ClinicalTrials.gov (www.clinicaltrials.org). Number of identification: NCT04148508 November 2019.
CRIS-Team Scopus Importer:2024-11-26
Keywords: Depression; Emotional competence; Mobile-health prevention; Personalization; Randomised controlled trial; Rumination; Well-being; Young people